Multi-omics analysis reveals a macrophage-related marker gene signature for prognostic prediction, immune landscape, genomic heterogeneity, and drug choices in prostate cancer - Zhu, Weian; Wu, Jianjie; Huang, Jiongduan; Xiao, Dongming; Li, Fengao; Wu, Chenglun; Li, Xiaojuan; Zeng, Hengda; Zheng, Jiayu; Lai, Wenjie; Wen, Xingqiao (Frontiers in Immunology, 2023)
Macrophages are not only components of the innate immune system, but also can play an anti-tumor or pro-tumor role in the tumor microenvironment due to their high heterogeneity and plasticity. Meanwhile, prostate cancer (PCa) is an immune-sensitive tumor, so it is of paramount significance to study the value of macrophage-associated networks in its prognosis and treatment. In this study, we identified 307 macrophage-related marker genes (MRMGs) through the comprehensive analysis of single-cell sequencing data and verified that macrophages had a strong influence on the development and progression of PCa based on consensus clustering of MRMGs in the TCGA database. Subsequently, a macrophage-related marker gene prognostic signature (MRMGPS) with 9 genes was further constructed by LASSO-Cox regression analysis and grouped according to the median risk score. Combined with experiments, survival analysis, and nomogram, it was revealed that MRMGPS has excellent predictive ability and was verified in the GEO-Merged cohort. More importantly, we also found a close relationship between MRMGPS and tumor immune microenvironment, therapeutic response, and drug selection by multi-omics analysis such as immune landscape, genomic heterogeneity, tumor stemness, drug sensitivity, and molecular docking. In conclusion, our study reveals the application value of MRMGPS in predicting the prognosis of PCa patients. It also provides a novel perspective and theoretical basis for immune research and drug choices for PCa.